2020
DOI: 10.1371/journal.pone.0218880
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sickle cell disease on susceptibility to HIV infection

Abstract: People with sickle cell disease (SCD) are reported to have low rates of HIV infection, slower progression to AIDS and lower HIV-associated mortality compared to the general population. Mechanisms of potential resistance to HIV in SCD are incompletely understood. We retrospectively reviewed the Transfusion Safety Study to compare HIV status between people with SCD and other congenital anemias who were routinely exposed to blood products during the high-risk period before HIV screening implementation. Non-SCD co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
(24 reference statements)
1
9
1
2
Order By: Relevance
“…While our results and others indicate HIV may worsen SCD, multiple studies have demonstrated a lower prevalence of HIV in individuals with SCD than comparison populations [11,12], and earlier studies described less severe HIV outcomes in patients with both diseases. Godeau et al reported none of 8 HIV positive SCD patients had progressed to AIDS, even without ART [16].…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…While our results and others indicate HIV may worsen SCD, multiple studies have demonstrated a lower prevalence of HIV in individuals with SCD than comparison populations [11,12], and earlier studies described less severe HIV outcomes in patients with both diseases. Godeau et al reported none of 8 HIV positive SCD patients had progressed to AIDS, even without ART [16].…”
Section: Discussioncontrasting
confidence: 74%
“…However, a retrospective study involving 1415 individuals with SCD from Brazil showed no relationship between HIV infection and clinical severity of SCD [ 8 ]. Contrary to this relationship of SCD potentially exacerbating HIV outcomes, some studies have indicated that SCD may protect against HIV infection [ 11 , 12 ] and others suggested an improvement in HIV progression and outcomes in individuals with SCD [ 9 , 13 ]. Therefore, additional studies are needed to elucidate whether the interaction between the two disease states might impact both HIV and SCD clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…AIDS was the cause of death in 5 out of 18 (23%) SCD patients with HIV, while it caused the death in 22 out of 36 (61%) of controls with HIV only. Our group has recently explored the epidemiology of HIV transmission by retrospectively reviewing the Transfusion Safety Study [27] to compare HIV status between SCD and other congenital anemia patients who were routinely exposed to blood products during the high-risk period before HIV screening implementation [28]. Congenital anemia patients demonstrated a higher risk of HIV acquisition compared to SCD (odds ratio 13.1; 95% confidence interval 1.6-108.9).…”
Section: Discussionmentioning
confidence: 99%
“…A mesma África subsaariana onde a DF é tão prevalente permanece como uma das mais afetadas também pelo Vírus da Imunodeficiência Humana (HIV), respondendo por aproximadamente 75% da população mundial de doentes (Piel et al, 2013); a prevalência do vírus é descrita em até 27% da população na Suazilândia, 21% em Botswana e 19% na África do Sul (Kharsany & Karim, 2016). Apesar da prevalência de DF e da infecção pelo HIV ocorrerem em populações semelhantes, e o fato de tanto o HIV quanto a doença falciforme serem preditores distintos de complicações como o acidente vascular cerebral (Imam, 2002), osteonecrose (Eholié et al, 2009), infecções (Kourtis et al, 2007) e hipertensão pulmonar (Barnett, Hsue, & Machado, 2008), artigos 2Caracterização da prevalência de HIV e risco de aquisição da doença entre portadores de doença falciforme no Brasil previamente publicados demonstram que o HIV é relativamente raro em portadores de doença falciforme (Agasa et al, 2010;Castro et al, 1990;Kelly S, 2019;. Kelly et al demonstraram em estudo com dados retrospectivos coletados de 1985 a 1993 em seis áreas nos EUA (quatro áreas com alta taxa de transmissão de HIV e 2 áreas com baixa transmissão de HIV) que os pacientes com doença falciforme apresentaram menor risco de infecção por HIV comparativamente a pacientes com talassemia e anemia de Blackfan-Diamond, ajustados os números de transfusões entre os dois grupos (Kelly et al, 2019).…”
Section: Introductionunclassified
“…Kelly et al descreveram menor expressão de CCR5 em 30 pacientes portadores de DF, comparativamente a 30 controles não portadores de DF. Esse receptor é sabidamente associado à transmissão de HIV (Kelly et al, 2019), o que causaria menor risco de transmissibilidade dentre portadores de DF comparativamente a não portadores de DF. Outro estudo correlacionou a maior prevalência (5,1%) do alelo mutante CCR5Δ32 na população com DF comparativamente aos controles saudáveis (1,3%), sendo que a presença desse alelo confere maior resistência à infecção pelo HIV .…”
Section: Introductionunclassified